The impact of Daniel's cognitive model on learning some basic gymnastic skills Art for students (Journal of the College of Basic Education, 2023)
Summary of the research:The research aims: Preparing learning units using Daniel's model in learning some basic skills in rhythmic gymnastics for female students, and identifying the impact of the prepared learning units in learning some basic skills in rhythmic gymnastics for female students in the research sample. The two researchers identified the research community by the intentional method with female students of the first stage, Al-Mustansiriya University, College of Basic Education / Department of Physical Education and Sports Sciences for the academic year (2022.2021), whose number is (140) students distributed into four divisions (A, B, C, D) to represent the college community, and the research sample was chosen Randomly and by lottery method from the two divisions (D + B), as division (D) represented the experimental group with (23) students, and division (B) represented the control group with (23) students. The two researchers excluded a number of female students in the research sample. The two researchers conducted equivalence for the two research groups with the skills under study, then an exploratory experiment was conducted, after which learning units were designed according to the Daniel model, and the experiment was applied for a period of 12 weeks, with one learning unit of 90 minutes, after which the experiment was carried out for two months and the test was conducted The two researchers used the statistical bag to reach the results, and in turn to the conclusions, the most important of which is that the Daniel model has a positive effect on the performance of some basic skills in rhythmic gymnastics for female students. And that Daniel's model helped reveal the students' self-abilities, skill level, and learning capabilities. Based on the conclusions reached by the two researchers, they recommend the preparation of special programs for teachers to train them to prepare the building of learning units using the Daniel model. Directing the teacher and the school to pay attention to the use of learning and teaching methods and to diversify them in a way that suits the need and content of different sports events. Emphasis on conducting research and studies on the Daniel model in the sports field for all events, sports and other skills.Keywords: Daniel's cognitive model: learning some basic skills: artistic gymnastics for female students.